Tribes in India: Their Socio-Economic Development through Art - Rani, Archana; Agarwal, Himanshu (Journal of Commerce and Trade, 2019)
Tribes are the keeper of nature. About 92 percent of the tribal community in India lives in dry, forested or hilly areas. They primarily depend on Agriculture and Minor Forest Produce (MFP) to sustain their life. The central part of India, The middle belt and the north-eastern states are the main adobe of tribal community in India. Tribal arts of India are deeply rooted in tradition and have evolved their own techniques and characteristics. Different Tribe arts are increasingly recognized as a independent art forms having distinct aesthetic beauty. All the art factors that give a distinct individuality to an artistic creation like composition, line, colour, texture and rhythm. In this research paper socio-economic development of Tribes in India through art has been analysed in depth. A special approach should have been formulated by the Indian Government with protection and integration of tribes as its principal objective of all-round development of tribes. Classification-JEL : D 63, F 43, I 15, I 25, J 11, J 15